1996
DOI: 10.1016/0925-4773(95)00462-9
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative expression of a cytoplasmically deleted mutant of XB/U-cadherin disturbs mesoderm migration during gastrulation in Xenopus laevis

Abstract: XB/U-cadherin is a maternal Xenopus cadherin which mediates interblastomere adhesion in early embryogenesis. In order to explore its role in gastrulation, we expressed a cytoplasmic deletion mutant of XB/U-cadherin (XB delta c38) under the control of the CMV promoter in Xenopus embryos. This truncated XB-cadherin fails to form complexes with catenins and does not mediate cell-cell aggregation as shown by transfection of mouse Ltk- cells. Injections of the deletion for XB/U-cadherin into the dorsal-marginal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Introductionfrom flies to mice (Babb and Marrs, 2004;Ciruna and Rossant, 2001;Kühl et al, 1996;Lee and Gumbiner, 1995;Wang et al, 2004). However, as already postulated in 1976 by Albert Harris (Harris, 1976) and theoretically demonstrated by G. Wayne Brodland (Brodland, 2003), recent experimental evidence indicates that, in addition to cell adhesion, cell affinity is influenced by intracellular mechanics and cell surface tension (Krieg et al, 2008;Ninomiya and Winklbauer, 2008).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Introductionfrom flies to mice (Babb and Marrs, 2004;Ciruna and Rossant, 2001;Kühl et al, 1996;Lee and Gumbiner, 1995;Wang et al, 2004). However, as already postulated in 1976 by Albert Harris (Harris, 1976) and theoretically demonstrated by G. Wayne Brodland (Brodland, 2003), recent experimental evidence indicates that, in addition to cell adhesion, cell affinity is influenced by intracellular mechanics and cell surface tension (Krieg et al, 2008;Ninomiya and Winklbauer, 2008).…”
mentioning
confidence: 95%
“…2). Both their extra-and intracellular domains are required for proper gastrulation movements (Kühl et al, 1996;Lee and Gumbiner, 1995). During Xenopus gastrulation, adherens junctions (AJs) formed by E-cadherin/catenin complexes are restricted to the outer ectodermal layer and contribute to the apical constriction of bottle cells (Merzdorf et al, 1998;Schneider et al, 1993).…”
Section: The Cadherinsmentioning
confidence: 99%
See 1 more Smart Citation
“…During Xenopus and zebrafish gastrulation, the over or underexpression of paraxial protocadherin (papc) leads to defects in convergence and extension of the forming embryonic body axis (Hukriede et al, 2003;Kim et al, 1998;Yamamoto et al, 1998). Furthermore, when XB/U-or EP/C-Cadherin function is blocked at the onset of Xenopus gastrulation, both mesodermal progenitor cell involution and migration, as well as germ layer separation, are affected (Kuhl et al, 1996;Lee and Gumbiner, 1995;Wacker et al, 2000). Finally, inactivating E-Cadherin in Xenopus and zebrafish embryos causes variable defects before and during gastrulation, including impaired prechordal plate formation and migration in zebrafish and ectodermal lesions in Xenopus (Babb and Marrs, 2004;Levine et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…How Wnt signalling is translated into convergent extension movements during gastrulation is poorly understood, but it clearly involves changes in the adhesive properties of cells, e.g. via regulated decreases in the activity of cell adhesion molecules such as cadherins (Kuhl et al, 1996;Marsden and deSimone, 2003). Non-canonical Wnt signalling seems not to be required for the segmentation clock, as we have shown that oscillator behaviour is normal in kny mutants (Fig.…”
Section: Rptpψ Is Required For Convergent Extension During Gastrulationmentioning
confidence: 84%